Study of the Tribological Properties of Paraffin and Polyethylene Wax as Antiwear Additives in Sesame Oil - Rodriguez Carmona, Esperanza; Delgado Tobón, Arnoldo Emilio; Aperador Chaparro, William Arnulfo (Scientia et Technica, 2019)
Vegetable oils were one of the main sources of lubricating oils before the appearance of oil. Currently, due to low thermal stability and oxidation, they are not used with the same frequency in the industrial sector. However, the different fatty acids that make up vegetable oils can significantly reduce the coefficient of friction. To optimize the lubrication, vegetable oils can be mixed with additives. In this research, a comparative study of the lubricating power of sesame oil with polyethylene wax and paraffin as additives was carried out. This property was evaluated by preventative wear tests and extreme pressure in a four-ball tribometer. The experimental results showed that for the preventive wear test the mixture with polyethylene wax has the smallest average diameter of the fingerprint, while for the extreme pressure test the mixture with paraffin gave a greater resistance to the applied load, obtaining a welding point to 32 Kg-F (314N) being greater than for pure oil and with polyethylene wax (24 Kg-F (235N)). In relation to the coefficient of friction the results obtained show that there is no difference between the pure oil and the mixtures with the different additives. From these results it can be concluded that the yield of sesame oil as a lubricant can be improved by mixing it with paraffin and polyethylene wax; however, the percentages added must be determined correctly.